Seroprevalence of Bartonella spp. infection in HIV patients in Catalonia, Spain - Pons, Immaculada (BioMed Central, 2008)
BACKGROUND: Although the first clinical descriptions of Bartonella infection were associated with immunocompromised patient with bacillary angiomatosis, we currently know that this organism is directly involved in diseases affecting a large number of patients, regardless of their immune status. Cat scratch disease, hepatic peliosis, and some cases of bacteraemia and endocarditis, are directly caused by some species of the genus Bartonella. The purpose of this study was to determinate the prevalence of IgG antibodies against Bartonella henselae and B. quintana in HIV patients and to identify the epidemiological factors involved. METHODS: Serum samples were collected from HIV patients treated at Hospital de Sabadell. Antibodies to B. henselae and B. quintana from 340 patients were examined by indirect immunofluorescence assay (IFA). Significance levels for univariate statistical test were determined by the Mann-Whitney U test and χ(2 )test. RESULTS: Of 340 patients, 82 were women and 258 men, with a median age of 42.21 ± 10.35 years (range 16–86 years). Seventy-six (22.3%) patients reacted with one or more Bartonella antigens. Of all the factors concerning the seroprevalence rate being studied (age, sex, intravenous drugs use, alcohol consumption, CD4 levels, AIDS, HCV, HBV, residential area), only age was statistically significant. CONCLUSION: A high percentage of HIV patients presents antibodies to Bartonella and is increasing with age.